ESG Performance, Board Gender Diversity, and Firm Value: The Moderating Role of Corporate Reputation - Muhammad Pondrinal; Elvira Luthan; Yosi Puspita Sari; Rahmat Wahyudi (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2026)
This study examines the effect of Environmental, Social, and Governance (ESG) performance and Board Gender Diversity on firm value, with corporate reputation proxied by Return on Assets as a moderating variable. The increasing importance of sustainability and governance practices has raised questions regarding their actual contribution to firm value, particularly in emerging markets where investor preferences may differ from developed economies. This study aims to provide empirical evidence on whether ESG and board diversity are valued by the market and whether corporate reputation strengthens these relationships. The research employs a quantitative approach using panel data regression on 57 non-financial firms listed on the Indonesia Stock Exchange over the period 2021 to 2024, resulting in 228 firm-year observations. The findings reveal that ESG performance and Board Gender Diversity do not have a significant effect on firm value. In contrast, corporate reputation has a positive and significant effect, indicating that profitability remains a key determinant of market valuation. Furthermore, the moderating effect of corporate reputation is not supported, suggesting that financial performance does not strengthen the relationship between ESG, board diversity, and firm value. These results indicate that investors in emerging markets place greater emphasis on financial outcomes than on sustainability and governance attributes. This study contributes to the literature by highlighting the gap between ESG implementation and market recognition, and suggests that firms need to align sustainability initiatives with financial performance to enhance firm value